Evaluation of Antibacterial and Antioxidant activity of methanol crude extract of Aspilia africana leaves: an in vitro approach - Adepoju, Oluwarinu; Omololu-Aso, Joseph (International Journal of Applied Sciences and Biotechnology, 2022)
Aspilia africana (Compositae) is one of such plants considered of great importance in the pharmacopeia of traditional medicine. This study was carried out to determine the antimicrobial and antioxidant potentials of its leaf methanol extract. leaf samples of Aspilia africana were collected, washed, air-dried, and processed to a fine powder in the microbiology laboratory of Obafemi Awolowo University, Nigeria. Crude extract of the leaf samples was done by the cold maceration technique using methanol solvents. Phytochemical analysis of the carried out using previously described technique, and in vitro antibacterial activities of concentrations 1.625-100 mg/ml and a standard antibiotic (Streptomycin) were tested on Staphylococcus aureus (MRSA), Bacillus stereothemophilus, Bacillus subtilis, and Micrococcus luteus, Escherichia coli, Klebsiella pneumonia, and Serratia marcensens, Proteus mirabilis by the agar diffusion test. The radical scavenging ability of the extract was determined using the stable radical DPPH (2,2-diphenyl-1-picrylhydrazyl hydrate). The phytochemical analysis of the crude extract of both plants revealed the presence of saponins, tannin, resin, phlobatannins, and phenols. The in-vitro antibacterial test of the methanol crude extract using the agar well diffusion method showed broad-spectrum activity. With a minimum bactericidal concentration of 30 and 75 mg/mL for Klebsiella pneumonia, and Bacillus subtilis respectively. In-vitro antioxidant activities using 2, 2–diphenyl-1-picrylhydrazyl assay indicate that the methanol leaves extract had higher activity than 92.23 µg/mL compared to standard drugs (Ascorbic acid 1.07 mg/mL) and IC50 at 4.66. This study concluded that Aspilia africana methanol crude extract exhibits dosage-dependent antioxidant antibacterial potential. Int. J. Appl. Sci. Biotechnol. Vol 10(2): 99-103.